The scorpion king [videorecording] - Sommers, Stephen, production; Russell, Chuck, direction ([S.l.] : Universal Pictures, 2001)
Inspired by the hugely successful Mummy series, The Scorpion King in an action-packed epic adventure filled with spectacular stunts and fights sequences. In a time of darkness and in the face of evil, one man dared to fight back. Utilising his combat skills as an assassin, wrestling sensation The Rock stars as the warrior who defies an empire to become a legend and unite a nation. Also staring the seductive Kelly Hu (Sunset Beach) and the powerful Michael Clark Duncan (Green Mile). Featuring a rocking soundtrack The Scorpion King smashes onto your screen offering a fast-moving, exciting and entertaining movie experience
Editor, Michael Tronick ; Screenplay by Stephen Sommers, William Osborne and David Hayter ; music by John Debney ; story by Stephen Sommers and Jonathan Hales
Staring: The Rock, Kelly Hu, Michael Clark Duncan
Keywords: Epic films; Fight in motion pictures; War films